Determinants of COVID-19 transmission in India: Issues and challenges - Ganesh Kumar Saya; Palanivel Chinnakali; K C Premarajan (Wolters Kluwer Medknow Publications, 2020)
The recent increase in trend of COVID-19 cases in India is an important public health issue. Cases reported vary in calendar time in different states and regions. Case presentations, its determinants and mediators such as behavioral and social factors may be different across and within countries. Although agent, host and environmental factors play a major role, there are other influencing factors for transmission of infection. Appropriate cost-effective prevention strategies such as social distancing, use of face mask and its implementation in the Indian context is a big challenge. Recent data available on the public domain was reviewed on various issues and challenges related to determinants of COVID-19 and its transmission in the Indian context. This review emphasizes to further strengthen prevention of infection transmission strategies at regional and state level by a combination of multiple strategies and robust surveillance system.